A comprehensive review of DC microgrid in market segments and control technique. Issue 11 (November 2022) - Ashok Kumar, A.; Amutha Prabha, N.
Abstract: DC- Microgrid has been widely developed for the distribution system. Energy utilizing device is easily integrated on DC – Microgrid to minimize losses in ease. In recent years, due to power distribution, -multiple energy sources are connected to DC-Microgrid. The connection of multi-sources deviates in power sharing and voltage performance is the significant challenges. To enhance the good quality of power and higher system efficiency, control strategies play a vital role. The main focus of this work is on DC-Microgrid control techniques. The conventional droop control has low current sharing and accuracy. To sort out the drawbacks, an improved primary controller is enhanced for better power sharing and accuracy. To achieve stable and dynamic current sharing scheme, secondary control strategies are reviewed. Further Multi-layer and Virtual control strategies for good voltage regulation have been reviewed. The purpose of this review is to represent on the hierarchical control structure of the DC microgrid and its three-level control architecture and this study explores distributed, centralized, decentralized, and hierarchical control techniques and discusses their strengths and weakness. Abstract : Microgrid, Market segment, Hierarchical control, Primary control, Secondary control, Territory control.